Hukum Memperdagangkan Barang Luqathah Perspektif Imam Syafi’i (Studi Kasus Di Jerantut Pahang, Malaysia) - Arni Nadira Binti Mohamad Roslan; Ahmad Zuhri (Universitas Medan Area, 2023)
This article was conducted to find out the extent to which students and the public out there understand the law of trading luqathah goods according to Imam Asy-Syafi'i, especially when they find items that have fallen. According to Imam Syafi'i, this issue is focused on finding found items (luqathah) when a major flood occurs. In order to approach this problem using data collection methods through observation, interviews and notes in the field. In analyzing the data, the technique used is the explanation of the analysis, namely the method of analyzing the data under study by explaining the data, explaining and combining all the answers from the research results, then analyzing them to obtain solid conclusions. This study concludes that the law of taking found objects (luqathah) according to Imam Asy-Syafi'i. conditions, namely: obligatory, sunnah, makruh, haram, jaiz or mubah.